Fibroblasts and mesenchymal stem cells: Two sides of the same coin? - Soundararajan, Mathangi; Kannan, Suresh (Journal of cellular physiology, 2018)
Mesenchymal stem/stromal cells (MSCs) have gained considerable popularity owing to the vast possibilities and lack of ethical constraints and risks normally associated with other stem cells, such as embryonic stem cells. However, they are morphologically indistinguishable from fibroblasts. This review aims to assess the similarities and differences between the two cell types, and the possible relationship between them. We found that the two cells seem almost identical with respect to their surface immunophenotype, proliferation, and differentiation capacities and even, to an extent, their gene expression profiles and immunomodulatory capacities. There are some differences in capability between the two cells, with MSCs being more efficient than fibroblasts. Even so, the similarities are so striking, that, if we were to follow the current criteria provided by the International Society for Cellular Therapy, fibroblasts ought to be named as MSCs. One promising marker is their DNA methylation profiles. Nonetheless, without any other marker to differentiate between the cells in the first place, it would be difficult to find a definitive marker. Interestingly, the differences observed between the two cells have also been observed between young and old MSCs. This also seems to be true of certain cell surface markers. Therefore, it is possible that fibroblasts are in fact aged MSCs and that the two cells are the same. Mesenchymal stem cells (MSCs) and fibroblast share many properties and it is possible that fibroblasts are in fact aged MSCs and that the two cells are the same.